Status of flying fox Bat (Pteropus spp.) in Vietnam - Son, Nguyen Truong; Thong, Vu Dinh; Tien, Pham Duc; Khoi, Nguyen Vu (Academia Journal of Biology, 2014)
Three species Pterosspus hypomelanus Temminck, 1853 Variable Flying Fox, Pteropus lylei K. Andersen, 1908 Lyle’s Flying Fox, and Pteropus vampyrus (Linnaeus, 1758) Large Flying Fox are now listed in the group of large bat of the world, in appendix II of CITES (Cites, 2005) and highly endangered extinct due to hunting from local people as well as being lost gradually their habitat. Recently, Vu Dinh Thong (2004) preliminary estimates about status of these three bat species and their distribution. Some surveys on three species Pteropus hypomelanus Temminck, 1853 Variable Flying Fox, Pteropus lylei K. Andersen, 1908 Lyle’s Flying Fox, and Pteropus vampyrus (Linnaeus, 1758) Large Flying Fox have been carried out from 2000 to 2009 and recorded the appearance of three species. These three bat species just distribute in some locations in the southern of Vietnam such as Doi pagoda, Cu Lao Dung area (Soc Trang province); Vo Doi nature reserve and some areas far from Cha La area about 15km (Tran Van Thoi district, Ca Mau province) and U Minh Thuong national park (Kien Giang province). The population of Pteropus vampyrus and Pteropus lylei are now recorded to be greatest in Doi pagoda (Soc Trang province) with the number of nearly 1500-2000 individuals, in which Pteropus lylei is more dominant species than Pteropus vampyrus. The second large population is recorded in Vo Doi National Park (Ca Mau province) with about 1000 individuals of Pteropus vampyrus and Pteropus lylei, U Minh Thuong national park (Kien Giang province) with the number about 300 individuals of Pteropus lylei and Pteropus vampyrus and in one site far from Cha La area about 10km (Ngoc Hien district, Ca Mau province) with about 1000 individuals of Pteropus lylei. As for Pteropus hypomelanus is just only recorded in Hon Khoai island (Ca Mau province), however, the size of this population is very small with about a few of tens of individuals observed. The greatest threatening risk for Pteropus spp. is: 1, due to hunting and trapping by local people to supply the speciallity restaurants in some areas in Soc Trang town (Soc Trang province), Ca Mau city (Ca Mau province) and Rach Gia city (Kien Giang province); 2, logging habitat which forest file is parimaliry cause when more than 2000 individuals of Pteropus vampyrus and Pteropus lylei was disappear at U Minh Thuong national park (Kien Giang province) during 2001 and they appear again in 2009 with small population about more then 300 individuals of Pteropus lylei and Pteropus vampyrus at the posision 09o36’12N, 105o06’28E in Canal 6, distance Hoa Mai lake about 1.5 km with belong center of U Minh Thuong national park (Kien Giang provinve).